2017
DOI: 10.4317/medoral.53714
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of primary stability of two implant designs in D3 bone

Abstract: Background: Primary stability (PS) is a key factor for implant survival rate and depends on implant design or bone quality. The aim of this study was to compare different thread designs implants, evaluating PS with periotest values (PV) and implant stability quotient (ISQ) values through resonance frequency analysis (RFA). Material and Methods: A total of 60 implants (Radhex®, Inmet-Garnick S.A., Guadalajara, Spain) were placed in freshly bovine ribs in vitro. Two designs were used: 30 tapered body with single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Coinciding with this result, many clinical studies also reported tapered shaped implants achieving higher ISQ values than cylindrical implants 16,19,20 . Concerning thread design, implants with more threads, deep threads, and micro‐thread designs were shown to positively influence the implant stability 8,21 . A split‐mouth clinical study by Gehrke and colleagues 22 also observed greater implant stability in tapered implants with wide pitch compared with cylindrical implants with narrow pitch.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Coinciding with this result, many clinical studies also reported tapered shaped implants achieving higher ISQ values than cylindrical implants 16,19,20 . Concerning thread design, implants with more threads, deep threads, and micro‐thread designs were shown to positively influence the implant stability 8,21 . A split‐mouth clinical study by Gehrke and colleagues 22 also observed greater implant stability in tapered implants with wide pitch compared with cylindrical implants with narrow pitch.…”
Section: Discussionmentioning
confidence: 73%
“…16,19,20 Concerning thread design, implants with more threads, deep threads, and micro-thread designs were shown to positively influence the implant stability. 8,21 A split-mouth clinical study by Gehrke and colleagues 22 also observed greater implant stability in tapered implants with wide pitch compared with cylindrical implants with narrow pitch. The reason why our result differs from the mentioned studies may be that TS/DT group had a higher number of female patient participants (10), while the CS/ST group had seven females.…”
Section: Discussionmentioning
confidence: 96%
“…For optimizing standardization, bone simulation blocks were used [ 17 , 18 ]. Also, there are cadaver and animal studies for primary stability evaluations in the literature [ 19 , 20 ]. Implant site preparation directly affects the mechanical implant stability [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, as bone tissue does not display homogenous density, bovine bone was preferred instead of polyurethane blocks that show homogeneous density ( 17 ). Nonetheless, it was therefore necessary to assess the bone quality in HU as already described ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%